Producción musical de la canción "No Make Up" del artista "Taggy" - Benalcázar Belalcázar, Bryan Andrés (2017)
This work documents the complete process of creating a musical work from how the idea was conceived to the final mix, passing through the design for the necessary graphic line that can properly complement the concept of the song. Describing broadly this thesis picks up step by step, from the beginning the path taken to achieve the final product, the theme chosen to be treated, the way in which the composition was both lyric and musical, the choice of instruments arguing each. Continuing with the reading of this work you will be able to find the stage of recording with detailed information about brands and models of instruments, microphones, microphone techniques, preamplifiers and everything related to this process, then we will see the stage of editing the shots taken A small introduction about the software chosen to develop this project. Making a parenthesis in the sound aspect of the project, you will find a space dedicated to the breakdown of the graphic line designed for the song, explaining its connection with the concept of the same. The last stage described in this text is the mix, where they will have information about the audio monitors, hardware devices and software their characteristics and configuration, arguing as they contribute to the final sonority of the song.